Structural Design and Performance Analysis of Large stroke Nanoscale Positioning Platform for Objective Lens - Zhu, Haonan; Cui, Huacheng; Lv, Yuehao; Cui , Liangyu (International Journal of Mechanical and Electrical Engineering, 2025)
This study addresses the demand for high-precision, large-stroke positioning in fields such as ultra-precision manufacturing, optical systems, and micro-nano positioning. A novel micro-nano positioning platform based on flexure hinges and a bridge-type amplification mechanism is proposed. The platform utilizes piezoelectric ceramics for actuation, with the bridge-type amplification mechanism amplifying the displacement. Theoretical analysis, parameter optimization, and finite element simulations were conducted to evaluate the system's performance. The design includes the selection of flexure hinges, development of guiding mechanisms, and analysis of the platform's static, dynamic, and kinematic performance. Results demonstrate that the platform achieves high-resolution, large-stroke positioning, meeting the application requirements of objective lens positioning and other high-precision scenarios. This study employs a piezoelectric objective positioning platform based on a bridge-type amplification mechanism. The platform utilizes piezoelectric ceramics as the driving force and compensates for the small displacement of piezoelectric ceramics through a bridge-type amplification mechanism. It integrates arc-shaped flexure hinges and a symmetric multi-link flexure guiding mechanism to ensure high-precision and decoupled displacement transmission. The platform is compactly designed with dimensions of 70mm × 55mm, achieving a maximum stroke of 0.2mm and a positioning accuracy of 5nm, meeting the requirements for objective lens positioning while accommodating certain load-bearing capabilities.